Tuning in the amplitude modulation rate domain - SĘK, A. P.; SKRODZKA, E. B. (Archives of Acoustics, 1998)
This paper is concerned with a certain form of masking that seems to exist in the modulation rate domain. It was shown that clearly audible changes in the amplitude of a 4 kHz sinusoidal carrier signal produced by a sinusoidal "probe" modulator were inaudible (masked) in the presence of amplitude changes in the same carrier produced by a "masking" modulator which was a 10 Hz wide band of white noise. This type of masking was most effective when the centre rate of the masking modulator was close or equal to the modulation rate of the probe modulator. The pattern of results showed a tuning effect in the modulation rate domain. These findings are generally consistent with the concept of a second stage of the filtering that may take place in the auditory system.